Angiogenic and growth factors in gastric cancer - Blank, Susanne; Deck, Catrin; Dreikhausen, Lena; Weichert, Wilko; Giese, Nathalia; Schmidt, Thomas; Ott, Katja (Journal of surgical research, 2015)
BACKGROUND: Antiangiogenic treatment is at the horizon in the palliative treatment of gastric cancer (GC), but data on proangiogenic biomarkers are still limited. The aim of this study was to analyze five proteins with a function in tumor angiogenesis: vascular endothelial growth factor (VEGF), angiopoietin-2 (Ang-2), follistatin, leptin, and platelet endothelial cell adhesion molecule 1 (CD31) in peripheral blood and corresponding tumor tissue. MATERIAL AND METHODS: From 2008-2010, tumor tissue (n = 76) and corresponding preoperative serum (n = 69) of patients with localized GC were collected; 45 had perioperative chemotherapy. Protein serum or tumor lysate levels of these factors were measured by an angiogenesis multiplex immunoassay and correlated with response and survival. RESULTS: Serum Ang-2 had prognostic relevance in the whole study population (P = 0.027). In subgroup analysis, serum VEGF and Ang-2 had prognostic relevance in primarily resected patients (P = 0.028; P = 0.048) but no association was found in neoadjuvantly treated patients. Follistatin concentration in the tumor tissue was associated with prognosis in all patients (P = 0.019). Tumor VEGF concentrations were correlated with histopathologic response (P = 0.011), with patients showing >50% remaining tumor having higher VEGF concentrations. The tissue Ang-2/VEGF ratio was significantly correlated with both clinical and histopathologic response (P = 0.029, P = 0.009). Additionally, the level of leptin in the tissue was associated with clinical response: nonresponding patients had higher leptin levels than those of responding patients (P = 0.032). CONCLUSIONS: Our results show the importance of angiogenetic factors in serum and tumor tissue in GC for prognosis and treatment response. Further trials in larger patient populations are warranted for a further evaluation of proangiogenetic factors as biomarkers in gastrointestinal cancer.
Published online: 26 November 2014
Gesehen am 10.08.2017